Job Stress among Workers: Implications and the Way Out - Ogunlade, A. A. (International Journal of Educational Management, 2022)
In recent times, job stress has attracted significant attention within various working places. In most cases job stress is attributable to negative situation, nonetheless, to function effectively and normally, we all need a certain degree of strength. This paper is basically theoretical, it discusses the causes of stress and its effects, before the question of job stress among workers in Nigeria could fully understood and tackled factors underlying such are properly identified and assessed issues relating to stress are also examined, different ways of reducing stress are also suggested.